NASUP Exemplary Mentor Award Winners – 2023 and 2024 - Christine Grabowski; Clara Outten; Charlene O'Brien (PDS Partners)
Purpose – The following narratives describe how successful relationships between mentors and pre-service and inservice teachers go beyond observations and feedback. The purpose is to share the multifaceted approach mentors take to support teacher candidates in generative ways so they can develop their potential as practitioners and how they nurture a culture of professional respect and understanding about how the school–university partnership supports teachers and students across the school and beyond the individual placement classrooms. Design/methodology/approach – The article contains first-person experiences of the recent National Association for School–University Partnerships (NASUP) Exemplary Mentor Award Winners for 2023 and 2024. Findings – The work of mentors facilitates the growth of pre-service and inservice teachers, empowering them to innovate and enjoy a sense of autonomy within their placement site and supports the growth of the university program, making the partnership more responsive to the needs of the pre-service and inservice teachers. These narratives are evidence of the power of the school–university partnership in growing teachers who exemplify the profession. Originality/value – A successful Professional Development Schools (PDS) partnership includes exemplary mentors who support pre-service teachers, in-service teachers and teacher candidates as they prepare for the profession.